Editorial: Why is South Africa’s food safety governance failing? - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2025)
In recent years South Africa has seen spectacular and distressing instances of food poisoning in which people have died after eating contaminated food from retail outlets. In 2024, 23 children died in Gauteng after eating “snacks purchased from spaza shops” (Parliament, 2024). Others became ill and many were hospitalised. Between September and November 2024, a total of 890 incidents of food-borne illnesses were reported across all provinces in South Africa (Ramaphosa, 2024). “In most cases, the illness started after food bought from spaza shops were consumed, but to date, no one has been held responsible” (Korsten, 2025:13).